Three new constructions of optimal linear codes with few weights - Cheng, Yingjie (2024)
Linear codes play a key role in widespread applications. In this paper, we propose three new constructions of linear codes. We give some sufficient conditions for the constructed linear codes to be optimal or distance-optimal in terms of the Griesmer bound. Three classes of distance-optimal linear codes with new parameters are presented. Under some constraints, we show that some of the presented linear codes have few weights.